Энергетика переходов В – Z- и Z–клубок в водных растворах поли(dG-dC) - Мревлишвили, Г.М.; Лапиашвили, Г.Н.; Мдзинарашвили, Т.Дж.; Горгошидзе, М.З.; Харатишвили, М.Г. (Биополимеры и клетка, 1990)
С использованием методов дифференциальной сканирующей калориметрии (ДСК), кругового дихроизма (КД) и УФ-спектрофотометрии исследовали переходы В–Z- и Z- спираль – клубок в поли (dG-dC). При 76 °С наблюдался обратимый переход, идентифицированный как В–Z-nepexoд. При 97 °С был зафиксирован гораздо более интенсивный по теплопоглощению переход Z-спираль –клубок. Рассчитаны термодинамические параметры этих переходов. З використанням методів диференційної сканувальної калориметрії (ДСК), кругового дихроїзму (КД) і УФ-спектрофотометрії досліджували переходи В-Z- і Z-спіраль-клубок у полі (dG-dC). За температури 76 °С спостерігався оборотний перехід, ідентифікований як В-Z-nepexід. За температури 97 °С зафіксовано набагато інтенсивніший за теплопоглинанням перехід Z-спіраль-клубок. Розраховано термодинамічні параметри таких переходів. Differential scanning calorimetry, CD- and UV-spectroscopy were used to study thermodynamics of the B-Z and Z-helix-coil transitions of poly(dG-dC). The experiments were performed under conditions of 0.5 mM water solutions of sodium cacodylate (pH 6.5) + 1 mM MgCl2 + 0.02 mM EDTA. The reversible transition of the polymer observed calorimetrically at 76 °C was identified as B-Z transition. The left-handed helix-coil transition was observed at 97 °C. The enthalpy of B-Z transition is small. A//Cai = 0.2 ± 0.02 kcal/mole bp, indicating a fine energy balance between the DNA left- and right-handed conformations in water solutions. The enthalpy of Z-helix-coil transition is A//Cai=10.1 ± l.l kcal/mole bp.